A study on effect of tobacco on semen quality - Dr. Bhumi Padia; Dr. Mukund Dhokiya (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Male infertility has a significant contribution in cases of infertility. Different habits among males i.e. smoking, tobacco chewing and alcohol intake have found adverse influence on sperm count and sperm motility. The mechanisms according to which tobacco affects spermatozoa are poorly understood. Some of the studies focused on the relation between cigarette smoking and the principal semen analysis, variable such as concentration, Morphology and Motility. In this study, we compared the sperm parameters-concentration and motility between tobacco consumers and tobacco non-consumers. Objectives: To identify the role of smoking and tobacco chewing in decreasing sperm count and motility. Methods: Total 100 semen samples from the cases of infertility reported at GMERS Medical College & Hospital were taken in this study. The results of tobacco chewers and smokers were studied and compared according to WHO guidelines, to that of tobacco non-consumers. Results: Out of 100 samples 59 showed decreased sperm count of which 41 men were tobacco consumers. 44 out of 100 samples showed decreased progressive motility, of which 29 men were tobacco consumers. Conclusion: Tobacco consumption either as smoking or tobacco chewing have a role in deteriorating the sperm quality and therefore in infertility of the male partners.